Synthesis, molecular docking studies and ADME prediction of some new triazoles as potential antimalarial agents - Brobbey, A.; Addotey, J. N.; Danquah, C. A.; et al. (Elsevier, 2023)
The challenges concerning the control of malaria remain due to the continuous emergence of drug resistant strains. Over the years, the use, misuse, and abuse of antimalarials have created a conducive environment for the development of resistant Plasmodium falciparum strains. We herein report on the synthesis, characterization and antimalarial activity of a library of seven novel 1,2,3-triazoles as part of the drug discovery campaign against drug-resistant Plasmodium falciparum. The interactions of the triazoles with plasmepsin II, plasmepsin IV, falcipain-2 and the heme detoxifying protein-all key proteins of Plasmodium falciparum degradosequesterome (Dsq) were also investigated by molecular docking. The compounds 3a-d, 4–6 were synthesized by CuAAC click reaction in good to excellent yields of 73–98% and characterized by melting point, UVvisible, infrared and nuclear magnetic resonance (1H and 13C) and MS techniques. Compounds 3a-d displayed high in vitro potency (IC50s: 0.62–22.11 ug/ml) against the chloroquine-resistant Dd2 lab strain of Plasmodium falciparum and low toxicity (SI > 1 except compound 4) to human erythrocytes. Computational studies indicated that the compounds 3a-3d had an absorption of 76–91%, and they were category III acute oral toxins (LD50 from 500 to 5000 mg/kg). The molecular docking study suggests that compounds 3a-d interacted with plasmepsin IV and the heme detoxifying protein with high affinity and a moderate affinity for falcipain-2. Keywords: Antimalarial; Click reaction; Docking; Plasmodium falciparum; Triazoles